KUALITAS AIR PADA LOKASI BUDIDAYA IKAN DI PERAIRAN DESA ERIS, DANAU TONDANO, KABUPATEN MINAHASA - Tumembouw, Sipriana S. (Sam Ratulangi University, 2012)
Eris Society in the village of utilizing the waters of Lake Tondano as a place to fish cultivation in floating net system and step on floating net karamba system. Karamba unit developments and floating net cages in the area of ​​cultivation step on the less controllable negative impact on the aquatic environment such as pollution of water quality. For this study aims to measure the quality parameters including pH, temperature, brightness and analyzed water quality parameters including turbidity, dissolved oxygen, ammonia and phosphate so that the water quality conditions in the Village of Lake Tondano District Eris Eris known. From the results obtained by the temperature at a depth of 0.5 meters from surface water ranged from 25.3 to 28.3 º C, at a depth of 0.5 meters from the lake bottom ranged from 24.7 to 28 º C, the brightness ranges from 182-325 cm, turbidity ranges from 7 - 16 NTU, the pH at a depth of 0.5 meters from the water surface ranged from 6.89 to 8.09, at a depth of 0.5 meters from the lake bottom ranged from 6.93 to 8.03, dissolved oxygen ranged from 7.10 to 7.52 mg / L, ammonia ranging from 0.03 to 0.14 mg / L, and phosphate ranged from 0.02 to 0.12 mg / L. Temperature, brightness, pH, dissolved oxygen and phosphate at the sites are still in good condition that is still in accordance with the water quality standard. For turbidity and ammonia has passed the threshold water quality standard. This is presumably due to domestic wastewater effluent from surrounding communities, causing decomposition which affects the water quality conditions. However the waters in the village of Eris can be used for aquaculture. This is evidenced by the persistent cultivation of fish in the Village District Eris Eris.